Making the Bible French: the Bible historiale and the medieval lay reader - Patterson, Jeanette (University of Toronto Press, 2022)
Frontmatter -- Contents -- List of Figures -- Acknowledgments -- Introduction -- 1 Making the French Bible, or Making the Bible French -- 2 Telling It Right: Confronting Reader Resistance -- 3 Soothing Listeners' Ears: Narrative Aesthetics and Poetic Faith -- 4 Les paroles dont je vous ay fait mention: The Bible historiale's Two Books of Job -- 5 The Patient Reader -- Conclusion: Asking the Right Questions -- Appendix: Table of Selected Manuscripts -- Notes -- Bibliography -- Index